Molecular Dynamics Simulations and Empirical Observations on Soy Lecithin Liposome Preparation - Rini Dwiastuti; Muhammad Radifar; Marchaban Marchaban; Sri Noegrohati; Enade Perdana Istyastono (Universitas Gadjah Mada, 2016)
Soy lecithin is a phospholipid often used in liposome formulations. Determination of water and phospholipid composition is one of the problems in the liposome formulation. This study is using molecular dynamics simulation and empirical observation in producing liposome preparations. Phospholipids 1,2-dilauroyl-sn-glycero-3-phosphoethanolamine (DLPE) were objected in molecular dynamics simulations using Coarse Grained Molecular Dynamics (CGMD) approaches. The result showed that the molecular dynamic simulations could be employed to predict the liposome size. The molecular dynamic simulations resulted in liposome size of 71.22 ± 2.54 nm, which was located within the range of the liposome size resulted from the empirical observations (95.99 ± 43.02 nm). Moreover, similar liposome forms were observed on both results of molecular dynamics simulations and empirical approaches.